Employee Relationship Management Practices and Perceived Job Satisfaction in Nepalese Small Businesses (NPRC Journal of Multidisciplinary Research, 2024)
Purpose – This study highlights the significance of efficient human resource management for organizational success by examining the effects of Employee Relationship Management (ERM) practices on job satisfaction in Nepali small businesses. Concentrating on small enterprises essential to Nepal's economy, the study aims to clarify how teamwork, open communication, suggestion programs, conflict resolution, employee empowerment, and decision-making involvement can enhance employee job satisfaction.Design/methodology/approach – A quantitative research approach was used, utilizing a descriptive and causal-comparative design. 175 employees from 20 small businesses in Lalitpur district of Nepal participated in a structured questionnaire survey that was used to gather data.Findings/Conclusions – The results show that job satisfaction and ERM practices are significantly correlated. The most substantial effects were demonstrated by teamwork, whereas empowerment and open communication had weaker but still favorable correlations. The study showed Employee Relationship Management (ERM) practices boost employee retention and job satisfaction and foster a positive work environment, eventually improving organizational performance.Implications – It gives policymakers and business executives valuable guidance and emphasizes how crucial it is for small businesses to prioritize ERM for long-term growth.  Future studies should investigate the relationship between ERM and job satisfaction using a larger and more varied sample, taking demographics and leadership philosophies into account.Originality/value - In the context of Nepali small businesses, this study adds to the conversation about employee well-being and organizational success. A unique aspect of this research is that it is the few to look at the relationship between ERM and employee job satisfaction in Nepali small scale businesses.